Beatific embodiment: An Augustinian appraisal of our end-time embodiment. Issue 4 (November 2022) - Luke, Sean
Abstract: In this paper, I seek to articulate a positive role for the body in our eschatological joy in God. I draw on Augustine's thought to argue that the body makes a positive contribution to our joy in God by being a pedagogy for our imaginations, training us to imagine the beautiful character of God in Christ through embodiment. While Augustine might seem like a surprising choice for this task, I argue that his concepts of ubique totus and the totus Christus provide fertile soil for the growth of an eschatological theology of the body.